A family of trade marks—stronger together. (26th May 2022) - Neophytou, John Peter
Abstract: McDonald's has successfully opposed a trade mark application for 'McVegan' on the basis that it was filed in bad faith and that it would have obtained an unfair advantage of McDonald's earlier 'Mc' family of marks.